New approaches to the treatment of patients with an overactive bladder and non-obstructive urge urinary incontinence - Kasimov S.S; Navruzov E.R (Academia One Publishing, 2023)
Overactive bladder (OAB) occurs in 20% of patients with various urinary disorders, while urge urinary incontinence is detected among a third of these patients. The goal of the work was to improve the results of treatment of women suffering from OAB with urge urinary incontinence and non-obstructive urination, by using a combination of drugs - an α1-adrenergic blocker and an M-anticholinergic blocker; study of the relationship between clinical and urodynamic manifestations of the disease. The state of microcirculation of the bladder mucosa was also studied before and after treatment. We examined and treated 40 women from 17 to 69 years old with a disease duration of one to 20 years. The patients were prescribed a combination of the α1-adrenergic blocker tamsulosin 0.4 mg at night and the M-anticholinergic blocker oxybutynin 5 mg in the morning daily for a month. After treatment, according to uroflowmetry and cystometry, the time of urination was shortened, the volume of urination increased and the maximum volumetric flow rate of urine increased; in addition, the cystometric capacity increased; involuntary detrusor contractions during the bladder filling phase (spontaneous or provoked) became fewer or were absent altogether. According to the results of ultrasound examination, the volume of residual urine decreased. According to the results of the treatment, a clinical effect was noted in 29 (73%) patients, urinary incontinence – in only 6 (15%) patients.
Keywords: oxybutynin; M-anticholinergic agent; overactive bladder; microcirculation